2020
DOI: 10.21098/bemp.v23i2.1173
|View full text |Cite
|
Sign up to set email alerts
|

External Debt, Institutional Quality and Economic Growth

Abstract: This paper addresses the gap in the literature by investigating the role of the institutional quality in the nexus of external debt and economic growth. By employing a dynamic panel data analysis, we found that the institutional quality plays some role in complementing the effect of external debt on a country’s economic growth. We also found that the negative effect of external debt and a country’s economic growth monotonically increases with the level of institutional indicator, which implies the possibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…In contrast, if the IRS is below its average value by between one and three standard deviations, the tipping point increases up to 150% and 180% of the debt-to-GDP ratio, respectively. These findings are in line with previous studies which investigated the relationship between public debt and growth in large panel data sets and found evidence for a varying debt threshold across countries (Caner et al, 2010;Afonso and Jalles, 2013;Kourtellos et al, 2013;Eberhardt and Presbitero, 2015;Duygu, 2018;Koroglu, 2019;Swamy 2020;Mohd Daud, 2020). Our results suggest that the level of uncertainty may be one of the factors explaining the observed threshold variation across countries.…”
Section: Source: Authors' Own Calculationssupporting
confidence: 92%
“…In contrast, if the IRS is below its average value by between one and three standard deviations, the tipping point increases up to 150% and 180% of the debt-to-GDP ratio, respectively. These findings are in line with previous studies which investigated the relationship between public debt and growth in large panel data sets and found evidence for a varying debt threshold across countries (Caner et al, 2010;Afonso and Jalles, 2013;Kourtellos et al, 2013;Eberhardt and Presbitero, 2015;Duygu, 2018;Koroglu, 2019;Swamy 2020;Mohd Daud, 2020). Our results suggest that the level of uncertainty may be one of the factors explaining the observed threshold variation across countries.…”
Section: Source: Authors' Own Calculationssupporting
confidence: 92%
“…Megersa and Cassimon [46] highlight that countries with better quality of governance and institutional environment have a higher public debt sustainability threshold and empirical evidence supports this conclusion [4]. However, few studies [49][50][51] find opposite results, i.e., that the negative effect of debt on growth increases as institutional quality improves. Our estimates suggest that the size of the expenditure multiplier may be another potential source of a heterogenous debt-growth relationship.…”
Section: General Resultsmentioning
confidence: 99%
“…The empirical results that we found regarding the relationship between institutional quality and external/public debt still use each indicator as an independent variable (Nguyen et al 2017;Nguyen et al 2018;Nguyen and Luong 2021;Mehmood et al 2021). Meanwhile, we did not find anyone who uses it as an index directly for external debt, and the closest relationship is to economic growth (Mensah et al 2018;Mohd Daud 2020;Samad et al 2022). We found that external debt has an inverse relationship with economic growth (Mehmood et al 2021).…”
Section: Institutional Quality and External Debtmentioning
confidence: 69%
“…Some studies stated significance (Nguyen et al 2017; and others did not have significance (Nguyen et al 2018). Meanwhile, using the institutional quality index, the results still vary greatly for each macroeconomy account (Mohd Daud 2020;Samad et al 2022). The variety of empirical results shows the importance of this research as a contribution.…”
Section: Macroeconomics Institutional Quality and External Debtmentioning
confidence: 99%